Elizabeth Costello ex machina: narrative tedium and metaleptic game in "Slow Man" - Valenzuela, Jose (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article explores, from the perspective of cognitive literary studies, the process of reception and difficult literary transportation of the figure of the real or empirical reader of the novel Slow Man by J. M. Coetzee. To do this, the metaleptic game produced by the appearance of its fictional writer, Elizabeth Costello, is addressed when it comes to explicitly combating throughout the pages of the novel the narrative tedium in which its protagonist, Paul Rayment, is immersed.